2005
DOI: 10.1152/ajplung.00451.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled carbon monoxide on acute lung injury in mice

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are major causes of morbidity and mortality in the intensive care unit, but despite continuing research few effective therapies have been identified. In recent years, inhaled carbon monoxide (CO) has been reported to have cytoprotective effects in several animal models of tissue injury. We therefore evaluated the effects of inhaled CO in three different in vivo mouse models of ALI. Anesthetized C57BL/6 mice were ventilated with oxygen in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
6
24
1
1
Order By: Relevance
“…Similar to our results, one study demonstrated that CO obtunded neutrophil recruitment after 4 h of mechanical ventilation; however, the direct injury was first primed with intravenous LPS, and progression of the injury beyond 4 h was not examined (7). In a study with conflicting results, pretreatment followed by continuous treatment with CO for 4 h did not affect lung inflammation or pulmonary neutrophil activation after direct exposure to intratracheal LPS (10). As suggested in that study, the lack of effectiveness may have been due to the severity and/or hyperacute response of the LPS model.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to our results, one study demonstrated that CO obtunded neutrophil recruitment after 4 h of mechanical ventilation; however, the direct injury was first primed with intravenous LPS, and progression of the injury beyond 4 h was not examined (7). In a study with conflicting results, pretreatment followed by continuous treatment with CO for 4 h did not affect lung inflammation or pulmonary neutrophil activation after direct exposure to intratracheal LPS (10). As suggested in that study, the lack of effectiveness may have been due to the severity and/or hyperacute response of the LPS model.…”
Section: Discussionsupporting
confidence: 84%
“…The majority of pulmonary studies has demonstrated efficacy with 250 (4,7,22,28,29) or 500 (5, 10, 36) ppm of CO delivered by either mechanical ventilation or spontaneous inhalation (12). Many of these studies use protocols that involve pretreatment with CO (4,10,22,29). Our study used the highest of the commonly reported doses without a pretreatment because this would be more relevant to the majority of clinical aspiration cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because neutrophils did not appear in the BAL of mice given Etx alone (Figure 6), and given that neutrophils were frequently found to be adherent to the endothelium of small parenchymal vessels (Figure 4), we believe these findings suggest that Etx-induced neutrophil influx into the lungs was limited to vascular sequestration. Using a dose of Etx that was 1/20th that used in our study, Ghosh and coworkers (29) recently arrived at a similar conclusion. In contrast, neutrophil penetration into the alveolar space after OA (with or without Etx) appears to be the result of either a breach in the alveolocapillary barrier or the establishment of a chemokine gradient caused by epithelial tissue damage.…”
Section: Etx and Oa Models Of Alisupporting
confidence: 76%
“…Although many of these reports point toward an anti-inflammatory function of CO in many systems, we still poorly understand the increasingly complex regulation and function of CO in pathophysiologic states. Recent studies suggesting the lack of cytoprotective effect of CO in some systems highlight this complexity (51)(52)(53). This current study attempts to examine one mechanism by which CO may regulate the inflammatory responses.…”
Section: Discussionmentioning
confidence: 98%